Bioengineering and Semisynthesis of an Optimized Cyclophilin Inhibitor for Treatment of Chronic Viral Infection. Issue 2 (19th February 2015) - Hansson, Magnus Joakim; Moss, Steven James; Bobardt, Michael; Chatterji, Udayan; Coates, Nigel; Garcia-Rivera, Jose A.; Elmér, Eskil; Kendrew, Steve; Leyssen, Pieter; Neyts, Johan; Nur-E-Alam, Mohammad; Warneck, Tony; et al.
Summary: Inhibition of host-encoded targets, such as the cyclophilins, provides an opportunity to generate potent high barrier to resistance antivirals for the treatment of a broad range of viral diseases. However, many host-targeted agents are natural products, which can be difficult to optimize using synthetic chemistry alone. We describe the orthogonal combination of bioengineering and semisynthetic chemistry to optimize the drug-like properties of sanglifehrin A, a known cyclophilin inhibitor of mixed nonribosomal peptide/polyketide origin, to generate the drug candidate NVP018 (formerly BC556). NVP018 is a potent inhibitor of hepatitis B virus, hepatitis C virus (HCV), and HIV-1 replication, shows minimal inhibition of major drug transporters, and has a high barrier to generation of both HCV and HIV-1 resistance. Highlights: Optimization and preclinical analysis of a bacterial natural product Combination of bioengineering and semisynthetic chemistry Preclinical analysis revealing potent antiviral activity Abstract : Hansson et al. describe the generation and preclinical analysis of a bacterial natural product with activity as a host-targeted antiviral drug. This was generated by a combination of biosynthetic engineering and semisynthetic chemistry.